Effect of Graphene Oxide Sheet Size on the Response of a Label‐free Voltammetric Immunosensor for Cancer Marker VEGF. Issue 10 (14th July 2020) - Elshafey, Reda; Brisebois, Patrick; Abdulkarim, Haya; Izquierdo, Ricardo; Tavares, Ana C.; Siaj, Mohamed
Abstract: Graphene and graphene oxide (GO) materials have attracted enormous attention in the biosensing field. Here, we report an evaluation of electrochemically reduced graphene oxide (ERGO) of different sheet sizes (0.45–0.7 μm, 0.7–2.5 μm and >300 μm) towards the voltammetric biosensing of vascular endothelial growth factor (VEGF) and the effect of the sheet size on the sensitivity of graphene‐based electrochemical biosensors. The degree of GO reduction and flakes sizes differ from one chemical route to another and ERGO with different sheet sizes have different amounts of edge and basal planes defects derived from oxygen containing functional groups. These could enhance or inhibit the sensitivity of the graphene‐based electrochemical sensors. The extent of reduction of GO to ERGO was found to vary with the sheet size. The decrease of the square wave voltammetry peak current of the [Fe(CN)6 ] 3−/4− couple upon VEGF binding to the immunosensor was employed as the sensor signal. It was found that the ERGO (0.7–2.5 μm) platform has the best performance for the detection of VEGF when compared to the other ERGO materials. The immunosensor showed a wide linear range of 0.1 pg mL −1 to 100 ng mL −1 and LOD of ∼0.1 pg mL −1 . The VEGF immunosensor was tested in human serum as a real sample application. The fabricated immunosensor exhibited high selectivity for VEGF against other protein interferences. Abstract :